(untitled) (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2021)
Globally, more than half the attempts at making a democratic constitution have failed to produce one. Another large number of constitutions have suffered the ignominy of having a draft made and implemented, but ultimately being rejected by the populace or political elites for failing to perform its intended functions. A curious case emerges in instances when would-be-autocrats draft authoritarian constitutions in democratic regimes. They do it rather successfully. Moreover, they do so without using force, with the consent of large sections of the society, and in ostensibly democratic ways. The question that then arises is how would-be-autocrats are more successful than their democratic counterparts in such ventures. Using three varied examples of authoritarian constitution-making from Hungary, Venezuela, and Turkey, this article will examine the ‘method and madness’ behind the success of would-be autocrat’s constitution-making endeavors and these authoritarian constitutions’ acceptance by the populace